The Influence of Earning Per Share (EPS) and Economic Value Added (EVA) on Wealth of Stock Holders at State-Own Construction Service Company Which Listed on IDX in 2014-2018 Period - Berina Annisa Tsaniya Ulfah; Feisal Fathul Pratama (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
During the Joko Widodo administration in the 2014-2019 period, construction service providers received large-scale projects for infrastructure development such as government buildings, roads and other infrastructure. This has led to a drastic increase in the stock price of construction service companies. With this signal given, investors see this as an opportunity to get profit in investing. Several other factors that are considered by investors in investing, namely financial performance such as Earning per Share (EPS) and Economic Value Added (EVA). The purpose of this study is to determine the development of EPS, EVA and Stock Return, and to prove the effect of EPS and EVA on Stock Returns in BUMN construction service companies listed on the IDX in the 2014-2018 period either partially or simultaneously. This research uses descriptive quantitative method. The data used is secondary data from the financial statements of construction service companies on the IDX in the 2014-2018 period by collecting data through documentation studies and literature studies. The design of the hypothesis used is multiple regression analysis, correlation coefficient, determination coefficient, partial test and simultaneous test. The results of the research partially prove that EPS has a significant negative effect on Stock Returns, while EVA does not have a significant effect on Stock Returns. Simultaneously, EPS and EVA have a significant effect on Stock Return.